The Influence of Distributive Justice and Moral Obligation on Tax Compliance of Star-rated Hotels in Ubud Area - Desak Made Ayu Darmayanti; I Putu Arnawa (Indonesian Journal of Banking and Financial Technology, 2025)
This study aims to determine the effect of distributive justice and moral obligation on taxpayer compliance of starred hotels in the Ubud area. The sample used was 35 taxpayers of starred hotels in the Ubud area with a saturated sampling method. This study uses quantitative data in the form of primary data. The data collection method uses a questionnaire with a Likert scale. The data analysis technique uses multiple linear regression using the Statistical Package for The Social Sciences (SPSS) version 25 application. The results of this study partially show that distributive justice has a negative effect, Moral obligation has a positive effect on taxpayer compliance of starred hotels in the Ubud area. The results simultaneously show that distributive justice and moral obligation together - together taxpayer compliance of starred hotels in the Ubud area.